2020
DOI: 10.1038/s41467-020-15424-4
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-specific antigen dynamics predict individual responses to intermittent androgen deprivation

Abstract: Intermittent androgen deprivation therapy (IADT) is an attractive treatment for biochemically recurrent prostate cancer (PCa), whereby cycling treatment on and off can reduce cumulative dose and limit toxicities. We simulate prostate-specific antigen (PSA) dynamics, with enrichment of PCa stem-like cell (PCaSC) during treatment as a plausible mechanism of resistance evolution. Simulated PCaSC proliferation patterns correlate with longitudinal serum PSA measurements in 70 PCa patients. Learning dynamics from ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 45 publications
2
75
0
Order By: Relevance
“…Pgp allocrites are amphiphilic and either electrically neutral or cationic. phenotypes are able to proliferate extensively, a process governed by eco-evolutionary dynamics (1,88).…”
Section: Pgp In Immunosurveillancementioning
confidence: 99%
“…Pgp allocrites are amphiphilic and either electrically neutral or cationic. phenotypes are able to proliferate extensively, a process governed by eco-evolutionary dynamics (1,88).…”
Section: Pgp In Immunosurveillancementioning
confidence: 99%
“…In a retrospective study, Buttigliero et al[ 75 ] showed that early PSA drop was related to a better overall survival and progression-free survival in mCRPC patients treated with abiraterone or enzalutamide (docetaxel-naïve or post-docetaxel setting). Finally, a mathematical model of PSA dynamics has been proposed to predict individual response to intermittent androgen deprivation therapy[ 76 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…West et al developed an evolutionary game theory model to determine the optimal timing of multi-drug adaptive therapies [ 23 ]. Brady-Nicholls et al developed patient-specific mathematical models that explain prostate cancer inter-tumor dynamics that can guide intermittent androgen deprivation therapy [ 24 ]. Mathematical modeling has shown the consequences of having spontaneous versus induced resistance responses to therapy [ 25 ].…”
Section: Introductionmentioning
confidence: 99%